2019
DOI: 10.1186/s12888-019-2042-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of depression among tuberculosis patients in Eastern Ethiopia

Abstract: Background Depression among tuberculosis patients, especially in settings with low economic status is common. Screening for depression in all levels of health facilities can identify patients who need support and treatment for depression. Objective The aim of this study was to assess the prevalence and associated factors of depression among tuberculosis patients in Eastern Ethiopia. Methods An institutional based cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
42
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 31 publications
21
42
1
6
Order By: Relevance
“…this might be due to younger population is more involve in their job and other household work and have more social support compared to older age group. This is consistent with Dasa et al 17 who found around 61% depression in older age group. Patients who has any comorbid condition found to have more depression (77.2%) (Table no6) compared to patients who has no comorbidity (43.5%).…”
Section: Discussionsupporting
confidence: 92%
“…this might be due to younger population is more involve in their job and other household work and have more social support compared to older age group. This is consistent with Dasa et al 17 who found around 61% depression in older age group. Patients who has any comorbid condition found to have more depression (77.2%) (Table no6) compared to patients who has no comorbidity (43.5%).…”
Section: Discussionsupporting
confidence: 92%
“…Drug side effects increase the prevalence of depression in pulmonary tuberculosis patients. This is in line with research (Dasa et al, 2019) finding that early diagnosis of tuberculosis and drug side effects increase the prevalence of depression in patients with pulmonary tuberculosis. Depression in tuberculosis patients was more common in patients with intensive phases.…”
Section: Discussionsupporting
confidence: 90%
“…In occupational characteristics, one's income was related to the prevalence of depression in tuberculosis. This is in line with research (Dasa et al, 2019) finding that low income increases psychological pressure due to inability to meet the needs of the patient's own life and that of their family. Regarding drug side effects, there were respondents who experienced severe side effects of drugs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comorbid mental illness is a notable, unrecognized challenge to TB care and prevention, particularly in high‐burden countries. Indeed, numerous reports have identified a high rate of mental illness, including depression and anxiety, among patients with TB . As such, there has been an increasing focus on the interplay between mental illness, including depression and chronic anxiety, and TB .…”
Section: Introductionmentioning
confidence: 99%